Preliminary findings of our institute on initial staging of breast cancer with FDG-18 PET/CT - Çakır, Tansel; Abamor, Evrim; Çakır, Abdulvahit; Basım, Pelin; Gezen, Cem; Evren, Müjgan; Atasever, Tamer (Springer, 2015)
[Abstract Not Available]
28th Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- October 10-14, 2015 -- Hamburg, Germany
WOS: 000363013203107
Keywords: Preliminary; FDG-18; Initial